Comprehensive Analysis of the Transcriptome-Wide m6A Methylome in Endometrioid Ovarian Cancer - Yang, Li; Chen, Xin; Qian, Xiang; Zhang, Jiejie; Wu, Meijuan; Yu, Aijun (Frontiers in Oncology, 2022)
Emerging studies have revealed that N6-methyladenosine modification is involved in the development of various cancers. However, the m6A modification pattern of endometrioid ovarian cancer (EOC) has not been demonstrated. In the present study, high-throughput sequencing combined with methylated RNA immunoprecipitation (MeRIP-seq) and RNA sequencing were used to obtain the transcriptome-wide m6A modifications of endometrioid ovarian cancer for the first time. The roles of methyltransferase-like 3 (METTL3) in EOC cell line COV362 were explored. In total, 39,237 m6A-modified peaks related to 17,082 genes were identified in the EOC group, and 52,848 m6A peaks representing 19,349 genes were detected in endometriosis group. Functional enrichment analysis revealed that m6A enriched genes were associated with tight junctions, cell adhesion molecules, platinum drug resistance, adherens junction, and more. METTL3 knockdown in the COV362 cells significantly decreased cell proliferation, promoted cell apoptosis, and induced cell cycle arrest at the G0/G1 phase. Our study presented the transcriptome-wide m6A modifications of endometrioid ovarian cancer for the first time and revealed various differentially expressed genes with methylated m6A modifications. This study may provide new directions for in-depth research of the underlying molecular mechanisms and signaling pathways of EOC development and progression.